The Diversity of Personnel Practices and Firm Performance - Pedro S. Martins (Institute for the Study of Labor (IZA), 2016)
Personnel economics tends be based on single-firm case studies. Here we examine the personnel practices of nearly 5,000 firms, over a period of 20 years, using detailed matched employer-employee panel data from Portugal. In the spirit of Baker et al. (1994a,b), we consider different dimensions of personnel management within each firm: worker turnover, the role of job levels and human capital as wage determinants, the dispersion of wages within job levels, the importance of tenure in terms of promotions and exits, and the scope for careers. We find a large degree of diversity in most of these practices across firms. Moreover, some personnel practices are shown to be robust predictors of higher levels of firm performance, even after controlling for time-invariant firm heterogeneity and other variables: low wage dispersion at low and intermediate job levels and a tight relationship between human capital variables and wages.
Keywords: M51; M52; J31; 330; personnel economics; job levels; wages; big data